IDENTIFIKASI LIMBAH ORGANIK PASAR SEBAGAI PAKAN TERNAK BABI - Redempta Wea (Politeknik Pertanian Negeri Kupang, 2010)
Identification of Organic Wastes from the Traditional Market as Pig Feed. This research was to evaluate the potency of organic wastes from the traditional market as pig feed. The research was a survey upon the availability of organic wastes in the Oeba traditional market by collecting data such as type, quantity and quality of organic wastes as the measurement variables. The data obtained were analyzed descriptively. The results showed that the organic wastes that were available in the Oeba traditional markets consisted of three groups, i.e. organic waste from animal products (available in 3 kinds), organic waste from marine products (available in 12 kinds), and organic waste from agricultural products (available in 35 kinds). Based on the quantity, quality and continuity of the organic wastes, there were only 6 kinds of the organic wastes that could be used as pig feed i.e. Tuna or cakalang fish (1040 gr/day), swordfish (686 gr/day), tembang fish (55, 86 gr/day), water spinach (164294, 57 gr/day), mustard greens (31949 gr/day), and rice bran (40000 gr/day).Keywords: organic waste, traditional market, pig feed